Antimicrobial and Antibiofilm Potential of Thymus vulgaris and Cymbopogon flexuosus Essential Oils against Pure and Mixed Cultures of Foodborne Bacteria - Joana Monteiro Marques; Susana Serrano; Hiba Selmi; Pedro Giesteira Cotovio; Teresa Semedo-Lemsaddek (MDPI AG, 2023)
The spread of pathogenic and food spoilage microorganisms through the food chain still faces major mitigation challenges, despite modern advances. Although multiple cleaning and disinfection procedures are available for microbial load reduction in food-related settings, microbes can still remain on surfaces, equipment, or machinery, especially if they have the ability to form biofilms. The present study assessed the biofilm-forming properties of pure and mixed cultures of foodborne and spoilage bacteria (Listeria monocytogenes, Enterococcus faecalis, Aeromonas hydrophila, Brochothrix thermosphacta), using polystyrene and stainless steel contact surfaces. Subsequently, the antimicrobial and antibiofilm properties of Thymus vulgaris and Cymbopogon flexuosus essential oils-EOs-were evaluated against these bacteria. Moreover, in silico prediction of the absorption and toxicity values of the EOs' major constituents was also performed, perceiving the putative application in food-related settings. Overall, biofilm formation was observed for all microbes under study, at different temperatures and both contact surfaces. In polystyrene, at 25 °C, when comparing pure with mixed cultures, the combination Listeria-Aeromonas achieved the highest biofilm biomass. Moreover, at 4 °C, increased biofilm formation was detected in stainless steel. Regarding thyme, this EO showed promising antimicrobial features (especially against A. hydrophila, with a MIC of 0.60 µg/µL) and antibiofilm abilities (MBEC of 110.79 µg/µL against L. monocytogenes, a major concern in food settings). As for lemongrass EO, the highest antimicrobial activity, with a MIC of 0.49 µg/µL, was also observed against L. monocytogenes. Overall, despite promising results, the in situ effectiveness of these essential oils, alone or in combination with other antimicrobial compounds, should be further explored.